Conceptions of adolescent mothers about the breastfeeding process - Joyce Mazza Nunes; Eliany Nazaré Oliveira; Neiva Francenely Cunha Vieira (Rev Rene)
One of the proposals of the Family Health Strategy is to ensure a good prenatal assistance and the breastfeeding guidelines. This study aims to identify the knowledge of adolescent mothers about breastfeeding and investigate how they experience it, its facilities and difficulties and sources of support. It was developed with seven mothers who received prenatal care at a Basic Health Unit in Sobral – CE, from October to November 2005. Information was collected through interviews during home visits. The results were organized in themes and analyzed according to the literature. We found out that teenage mothers have consistent knowledge of breastfeeding. For many of them, this moment is pleasant, but for others it is experienced as having good and bad moments. Most of them did not have trouble breastfeeding. The support of the family was important in the breastfeeding process.